Heterogeneidade produtiva a na agricultura brasileira: Elementos estruturais e dinâmicos de trajetória produtiva recente - Gesmar Rosa dos Santos; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study addresses the structural heterogeneity and production of Brazilian agriculture. Economic indicators of labor productivity, specialization and income concentration in agriculture are analyzed. The structural heterogeneity can be evidenced through the persistence of economic differences that hinder economic development inclusive. The central objective is discussing the structural and productive issues that lead to heterogeneity in agriculture. We show a high specialization and concentration of income in a few group of products and resources that affect sustainable development of the sector in its various dimensions. When analyszed from the standpoint of structural heterogeneity, public policies have been failures in both themes: diffusion of technology to producers as well as the incentive to gain in scale. Interregional disparities also highlight some weaknesses of the majority of producers, as well as their different trajectory of agricultural production.
Keywords: Q10; Q12; Q16; 330; heterogeneity; productivity; specialization and concentration; Landwirtschaft; Arbeitsteilung; Agrarstruktur; Brasilien